Assessing agricultural market integration of Cambodia within and beyond ASEAN - Ajmani, Manmeet Singh; Joshi, Pramod Kumar; Roy, Devesh; Renjini, V. R. (International Food Policy Research Institute, 2019)
In this paper, we address the question of the agricultural market integration of Cambodia within the Association of Southeast Asian Nations (ASEAN), and its other top trading partners. Focusing on agricultural trade, we use two indicators, namely, “Trade Potential” and “Competition Indices,” to assess the nature and extent of the integration. More specifically, we identify the exports of Cambodia with high export potential and comparatively low competition in export markets. Higher trade potential with lower competition (value or volume) indicates an opportunity of higher returns for agricultural producers. In the case of Cambodia, “maize,”and “starches” are identified as high-potential exports with lower intra-ASEAN competition. There is also scope for regional cooperation in traditional exports such as “rice,” “manioc (cassava),” “molasses,” and “pepper” between Cambodia and other Southeast Asian countries for which both the export potential and intra-ASEAN competition are high. Finally, to demonstrate the upward movement in the value chain, possibly due to quality upgradation, we present the dynamics of the unit values of Cambodia’s agricultural exports.